2020
DOI: 10.1186/s12884-020-03296-x
|View full text |Cite
|
Sign up to set email alerts
|

Burden of stillbirths and associated factors in Yirgalem Hospital, Southern Ethiopia: a facility based cross-sectional study

Abstract: Background Stillbirth is an adverse pregnancy outcome of public health importance causing considerable psychosocial burden on parents and their family. Studies on stillbirth are scarce in southern Ethiopia. An assessment of stillbirths and associated factors in health care settings helps in devising strategies for tailored interventions. Therefore, we assessed the burden of stillbirths and associated factors in Yirgalem Hospital, southern Ethiopia. Methods A facility based cross-sectional study was conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
3
10
1
Order By: Relevance
“…of neonatal deaths similar to studies in other settings [25,26]. Correspondingly with other studies [27,28], in our study, we found that old age, multiparity, history of stillbirths, and induction of labor were high among women who experienced stillbirths. The findings may indicate the inadequacy of maternity care and the need for specialized care for women with a history of previous pregnancy loss.…”
Section: Plos Onesupporting
confidence: 91%
“…of neonatal deaths similar to studies in other settings [25,26]. Correspondingly with other studies [27,28], in our study, we found that old age, multiparity, history of stillbirths, and induction of labor were high among women who experienced stillbirths. The findings may indicate the inadequacy of maternity care and the need for specialized care for women with a history of previous pregnancy loss.…”
Section: Plos Onesupporting
confidence: 91%
“…Prior studies found that neonate's whose mother had history of stillbirth were at higher risk of expriencing an adverse perinatal outcomes in succeeding pregnancies [19,22,29,30]. Our study found a result in line with the above evidence.…”
Section: Discussionsupporting
confidence: 89%
“…A total of 134 cases and 268 controls were participated in this study to make a response rate of 100% for both cases, and controls. The median (IQR) age of the neonate's mother was for controls and for cases was equally represented 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The majority of the neonate's mother for cases (97.8%) and controls (91.4%) were married.…”
Section: Socio-demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…This study revealed that the prevalence of stillbirth was 12.5% (95% CI: 8.1–14.6), higher than the study conducted in Ethiopia, Aksum (3.68%), Yirgalem Hospital (9.2%), Nigerian referral hospitals (3.96%) and India (4.0%), Pakistan (1.6%), overall in Pakistan (5.69%), and Babol, Northern Iran (10.51%) 6 , 14 , 28 , 43 - 45 . This difference might be due to the study design, sociodemographic characteristics of study participants, and/or the technological differences.…”
Section: Discussionmentioning
confidence: 55%